Near real-time determination of B.1.1.7 in proportion to total SARS-CoV-2 viral load in wastewater using an allele-specific primer extension PCR strategy. (15th October 2021) - Graber, Tyson E.; Mercier, Élisabeth; Bhatnagar, Kamya; Fuzzen, Meghan; D'Aoust, Patrick M.; Hoang, Huy-Dung; Tian, Xin; Towhid, Syeda Tasneem; Plaza-Diaz, Julio; Eid, Walaa; Alain, Tommy; Butler, Ainslie; et al.
Highlights: Incidence proportion of Variants of Concern can be estimated via wastewater. Allele and lineage specificity is possible with single locus primer extension qRT-PCR. High correlation of VOC-positive clinical cases and VOC-specific wastewater signal. Allows near real-time monitoring of VOC infection dynamics in a population. Abstract: The coronavirus disease 2019 (COVID-19) pandemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has claimed millions of lives to date. Antigenic drift has resulted in viral variants with putatively greater transmissibility, virulence, or both. Early and near real-time detection of these variants of concern (VOC) and the ability to accurately follow their incidence and prevalence in communities is wanting. Wastewater-based epidemiology (WBE), which uses nucleic acid amplification tests to detect viral fragments, is a reliable proxy of COVID-19 incidence and prevalence, and thus offers the potential to monitor VOC viral load in a given population. Here, we describe and validate a primer extension PCR strategy targeting a signature mutation in the N gene of SARS-CoV-2. This allows quantification of B.1.1.7 versus non-B.1.1.7 allele frequency in wastewater without the need to employ quantitative RT-PCR standard curves. We show that the wastewater B.1.1.7 profile correlates with its clinical counterpart and benefits from a near real-time and facile data collection and reporting pipeline. This assay can be quickly implemented within a current SARS-CoV-2 WBE framework with minimal cost; allowing early and contemporaneous estimates of B.1.1.7 community transmission prior to, or in lieu of, clinical screening and identification. Our study demonstrates that this strategy can provide public health units with an additional and much needed tool to rapidly triangulate VOC incidence/prevalence with high sensitivity and lineage specificity. Graphical abstract: Image, graphical abstract